(untitled) (International Journal of Environmental Sciences, 2025)
Background: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease worldwide and the leading cause of liver-related morbidity and mortality. We aimed to investigate the function of the PNPLA3 gene polymorphism as a non-invasive biomarker for NASH diagnosis. Because invasive diagnostic procedures have limits and non-invasive methods are inaccurate, the primary focus of attention for screening, classifying severity, and tracking the advancement of NASH and liver fibrosis has shifted to the discovery and validation of noninvasive biomarkers. Method: Study populations, in whom NAFLD was diagnosed using an imaging method in the absence of excessive alcohol consumption and viral hepatitis. . In a case-control study, 50 histologically confirmed NAFLD patients and 30 matched healthy controls were genotyped for PNPLA3 rs738409 using real-time PCR. Clinical, biochemical, and histological data were compared across genotypes. Results: The G allele was significantly more frequent in NAFLD patients (p < 0.001) and correlated with higher ALT, AST, BMI, and histological severity (steatosis, inflammation, fibrosis). The GG genotype conferred the highest risk The CC genotype lowered the risk of non-alcoholic fatty liver disease by 63%, while the CG genotype increased the risk by 32% and NASH by 30%. GG genotype carriers had a 34% and 40% greater incidence of non-alcoholic fatty liver and NASH, respectively. Individuals with CG + GG genotypes had a 66% higher chance of developing the disease and a 70% higher risk of NASH. Conclusion: PNPLA3 rs738409 is strongly associated with NAFLD and NASH severity. Genotyping may serve as a non-invasive risk stratification tool in clinical practice. Our study confirmed that this genotype can be used as a non-invasive biomarker. But also, Future research may investigate the influence of genetic and environmental factors on tissue damage levels, as well as the impact of this gene on fibrosis and liver cirrhosis. Future genomic analyses through fine mapping or comprehensive sequencing may uncover additional genetic determinants within the PNPLA3 locus.